MANAJEMEN KONFLIK INTERPERSONAL DI SEKOLAH - Ahmad Muslim (Universitas Pendidikan Mandalika, 2014)
This article is written to find out the parties and causes of interpersonal conflict, interpersonal conflict management strategies, organizing in interpersonal conflict management, and procedures in interpersonal conflict management. The results of the thinking are (1) conflicting parties involve individuals inside and outside the school environment with various causes of conflict, (2) the management strategy used (3) management organization consists of two stages, namely the determination of the parties managing the conflict and tasks to be carried out and the determination of the quality of the conflict.